QseC Mediates Osmotic Stress Resistance and Biofilm Formation in Haemophilus parasuis - He, Lvqin; Dai, Ke; Wen, Xintian; Ding, Lingqiang; Cao, Sanjie; Huang, Xiaobo; Wu, Rui; Zhao, Qin; Huang, Yong; Yan, Qigui; Ma, Xiaoping; Han, Xinfeng; et al. (Frontiers in Microbiology, 2018)
Haemophilus parasuis is known as a commensal organism discovered in the upper respiratory tract of swine where the pathogenic bacteria survive in various adverse environmental stress. QseC, a histidine protein kinase of the two-component regulatory systems CheY/QseC, is involved in the environmental adaptation in bacteria. To investigate the role of QseC in coping with the adverse environment stresses and survive in the host, we constructed a qseC mutant of H. parasuis serovar 13 strain(△qseC), MY1902. In this study, we found that QseC was involved in stress tolerance of H. parasuis, by the △qseC exhibited a decreased resistance to osmotic pressure, oxidative stress, and heat shock. Moreover, the △qseC weakened the ability to take up iron and biofilm formation. We also found that the QseC participate in sensing the epinephrine in environment to regulate the density of H.parasuis.